2001
DOI: 10.1002/1521-3773(20011001)40:19<3589::aid-anie3589>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of an Enantioselective Enzyme through Combinatorial Multiple-Cassette Mutagenesis

Abstract: Recombinant methods work exceedingly well in the directed evolution of an enantioselective enzyme. For the kinetic resolution of the ester rac‐1 by a lipase [Eq. (a)] three steps were applied: 1) Generation of mutants by the error‐prone polymerase chain reaction (epPCR), 2) identification of “hot spots” in the enzyme by epPCR and simplified combinatorial multiple‐cassette mutagenesis (CMCM), and 3) extension of the process of CMCM to cover a defined region of protein sequence space. From lass then 40 000 enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
116
0
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(128 citation statements)
references
References 4 publications
0
116
0
12
Order By: Relevance
“…Therefore, esterases in general are attractive tools for biocatalytic applications, such as chiral synthesis of pharmaceuticals or agrochemicals (17). Recently, several bacterial esterases have been subjected to laboratory evolution to obtain enzymes with improved properties, including substrate specificity or enantioselectivity (2,33,35). The primary aim of the present study was to combine the advantages of cellular surface display with the attractive features of a bacterial esterase (4).…”
mentioning
confidence: 99%
“…Therefore, esterases in general are attractive tools for biocatalytic applications, such as chiral synthesis of pharmaceuticals or agrochemicals (17). Recently, several bacterial esterases have been subjected to laboratory evolution to obtain enzymes with improved properties, including substrate specificity or enantioselectivity (2,33,35). The primary aim of the present study was to combine the advantages of cellular surface display with the attractive features of a bacterial esterase (4).…”
mentioning
confidence: 99%
“…Numerous structure-guided and directed evolution strategies have been used in search of enzyme variants that exhibit high catalytic rates with poor or inactive substrates of the parental enzyme (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As impressive as these successes have been, the engineering of enzymes that exhibit turnover rates and selectivities with new substrates comparable to their natural counterparts has proven quite a challenge, especially when considering those enzymes for which a genetic selection strategy is not possible.…”
mentioning
confidence: 99%
“…In a recent comprehensive study, Aaron et al (12) demonstrated that the evolution of higher activity toward poor substrates did not impair the parental catalytic activity, and, therefore, the evolved enzymes exhibited greater promiscuity. Enzymes evolved for higher substrate enantioselectivity often exhibit lower specific activities toward their new substrates relative to their respective parental enzymes (13)(14)(15). Similarly, the evolution of highly active variants of aspartate aminotransferases capable of accepting branched or aromatic amino acid substrates was accompanied by a relaxation of the substrate selectivity (16,17).…”
mentioning
confidence: 99%
“…LipA is an extracellular lipase produced by stationary-phase cells as a virulence factor, and it is also an important biocatalyst. Directed evolution using several random and directed mutagenesis methods ultimately resulted in a variant with high (S)-enantioselectivity that contained six amino acid substitutions (90). With the aid of the wild-type LipA crystal structure (72), molecular dynamics simulations were carried out to predict the roles of the six amino acids, and the main source of enantioselectivity was traced to the cooperative influence of two of the six mutations, namely, S53P and L162G (12).…”
Section: Pseudomonas Physiological and Metabolic Diversitymentioning
confidence: 99%